Pharmacognostic and Phytochemical Evaluation of Euphorbia neriifolia: A Therapeutic Perspective - Kaur, Navneet; Rani, Sapna; Saini, Vipin (Journal of Neonatal Surgery, 2025)
Based on its use in traditional medicine, Euphorbia neriifolia is a well-known medicinal plant with substantial therapeutic potential. The pharmacognostic traits, phytochemical profile, pharmacological activity, and quality control methods related to this adaptable species are examined in this paper. Terpenoids, flavonoids, alkaloids, and phenolics are among the many bioactive substances found in the plant that give it a variety of pharmacological qualities, including anti-inflammatory, antioxidant, antimicrobial, anticancer, antidiabetic, immunomodulatory, hepatoprotective, and wound-healing effects. Its identification and standardisation are based on pharmacognostic tests, which guarantee the use of genuine plant material. Compounds like taraxerol and euphol have been found by phytochemical studies as important contributions to its bioactivity. For extracts to be consistent from batch to batch, chromatographic fingerprinting methods such as TLC, HPLC, and GC-MS are crucial. Quality control measures, such as the assessment of physicochemical properties, toxicity testing, and conformity with regulatory standards, play a key role in insuring safety and efficacy. Even though E. neriifolia has a lot of potential for therapeutic development, issues including its inconsistent phytochemical makeup and scant clinical data call for more study. In order to effectively utilise Euphorbia neriifolia's medicinal potential, this review emphasises the significance of fusing traditional knowledge with contemporary scientific methodologies. It also lays the groundwork for the plant's use in the creation of plant-based medications.